Too many to fail? Inter-enterprise arrears in transition economies - Antje Hildebrandt (Bank of Finland, Institute for Economies in Transition (BOFIT), 2002)
In advanced market economies, the use of trade credits is an important way of short-term financing and generally considered as being part of normal business practice.Some transition economies, however, have experienced a rapid accumulation of trade credits which have led to interlocking webs of arrears and collective bailouts by the government.In this paper, firm-level data is used to test whether trade credits are just part of normal business practice comparable to more advanced market-economies or whether trade credits represent a systematic phenomena supporting soft budget constraints of firms in transition.The results suggest that trade credits are not just normal business practice but that they can have negative spill-over effects on other firms by worsening their financial situation.We conclude that the problem of interlocking effects is more pronounced in countries with less developed institutions, low financial intermediation and, overall, no credible commitment to market economic reforms.
URN:NBN:fi:bof-201408072207
Keywords: P31; P35; L10; 330; inter-enterprise arrears; soft budget constraints; transition economies